(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Curcumin being component of Curcuma longa is a natural polyphenol. Observing on a chemical level, curcumin is a natural polyphenol which is denominated (1E,6E)-1,7-bis(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene3,5-dione) which is usually extracted through the rhizomes of Curcuma longa. Structurally, it is composed of a trio of chemical identities on a molecular level: dual aromatic ring system. The objective of the research was to design, development and characterization of herbal drug loaded albumin nanoparticles to cure parkinson’s disease for improving and increasing the therapeutic efficacy and also reducing the frequency of dose. The optimized formulations were obtained after applying the design of experiment which was Box Behnken method where three independent variables; polymer concentration, stirring time, crosslinker concentration were selected. Curcumin nanoparticles loaded with albumin were formulated by ph coacervation method in which ethanol was used as desolvating agent along with a cross linking agent (Glutaraldehyde) and albumin as the polymer. The particle size and polydispersity index of curcumin loaded albumin nanoparticles was measured via dynamic light scattering technique. Drug release research conducted using in vitro method over the duration of 24 hours. Ex vivo drug release study of the albumin nanoparticles was performed using nasal membrane of goat. It has been shown that in case of hydrophilic matrices, swelling of polymer occurs followed by release of drug by diffusion which was best explained by Korsmeyer- peppas equation, which indicates drug release through diffusion which occurs by swelling of polymer matrix and remained constant throughout the release of drug in body. By virtue of particle size, the designed nanoparticles effortlessly goes into the nasal mucosa.